Genetic covariation between brain volumes and IQ, reading performance, and processing speed - Betjemann, Rebecca S. (2010)
Although there has been much interest in the relation between brain size and cognition, few studies have investigated this relation within a genetic framework and fewer still in non-adult samples. We analyzed the genetic and environmental covariance between structural MRI data from four brain regions (Total Brain Volume, Neocortex, White Matter, and Prefrontal Cortex), and four cognitive measures (Verbal IQ (VIQ), Performance IQ (PIQ), Reading Ability, and Processing Speed), in a sample of 41 MZ twin pairs and 30 same-sex DZ twin pairs (mean age at cognitive test = 11.4 years; mean age at scan = 15.4 years). Multivariate Cholesky decompositions were performed with each brain volume measure entered first, followed by the four cognitive measures. Consistent with previous research, each brain and cognitive measure was found to be significantly heritable. The novel finding was the significant genetic but not environmental covariance between brain volumes and cognitive measures. Specifically, PIQ shared significant common genetic variance with all four measures of brain volume (r(g) = .58 –.82). In contrast, VIQ shared significant genetic influence with Neocortex volume only (r(g)= .58). Processing Speed was significant with Total Brain Volume (r(g) = .79), Neocortex (r(g) = .64), and White Matter (r(g) =.89), but not Prefrontal Cortex. The only brain measure to share genetic influence with Reading was Total Brain Volume (r(g) =.32), which also shared genetic influences with processing speed.